The Effect of Ambient Temperature on Migraine Disease: A Scoping Review - James Kelbert; Joshua A. Tobin (Brain and Behavior)
ABSTRACT Introduction Ambient temperature changes are hypothesized to affect migraine attacks, but few published primary articles assess such hypotheses. The authors examine the current germane literature and suggest further research. Methods A literature search was conducted on September 23, 2023, in PubMed, Embase, and Scopus using the search terms temperature [ti] AND (headach*[ti] OR migrain*[ti]). Rayyan was utilized for duplicate detection and removal and for abstract screening. Conflicting assessments of records were resolved by consensus, and full text analysis was performed. Data was extracted by hand and tabulated. Results Four studies met the inclusion criteria, with an additional eight found through citation analysis that analyzed tens of thousands of patients with migraine disease overall. Six studies demonstrated an association between temperature or temperature changes and migraine disease. One study identified individuals whose migraine attacks were temperature sensitive, but the association was lost when examining the whole population. The remaining five did not find any significant relationship. Every study examining patients on an individual level found a relationship between temperature and migraine disease. Studies in colder geographic areas had a greater propensity to identify cold as a trigger. Conclusion Current data are conflicting. Temperature may be a migraine disease trigger in a subgroup of people with migraine. Lower temperatures may trigger more migraine attacks in colder climates within a subset of people with migraine. Uncontrollable factors such as air pollution, barometric pressure, and humidity are confounding variables that impede such research. Additional studies could include indoor temperature or thermostat settings during the day and night to further stratify the effects of temperature.